‘Obama, Please Tax Me!’: Architecture and the Politics of Redistribution - Tom Avermaete; Dirk van den Heuvel (Footprint)
This issue of Footprint is based on the conference session ‘The European Welfare State Project – Ideals, Politics, Cities and Buildings’ as organized by the editors at the first EAHN Conference in Guimarães, Portugal in 2010, and as elaborated in the second EAHN Conference in Brussels, Belgium in 2012 (together with Mark Swenarton). These sessions were proposed as part of the research programme ‘Changing Ideals – Shifting Realities’ at the TU Delft, which aims to further disclose, map and question the architectural culture of the second half of the twentieth century.